Problem Based Learning (PBL) in the Development of Emotional Intelligence of University Students - Luy-Montejo, Carlos (2019)
This article deals with the effect of Problem Based Learning (PBL) in the development of the emotional intelligence of first-semester students in a private university in Lima. To achieve this purpose, an applied research was carried out, using the experimental method (quasi-experimental design), given that the independent variable (PBL) will be manipulated so that it produces an effect on the dependent variable (Emotional Intelligence), which will be measured. To do this, a sample of 48 students was taken, it was divided into two groups: one of control (24) and the other one experimental (24) of a total population of 1281 freshmen. For the collection of data, the Bar-On Emotional Intelligence Inventory (I-CE) test was used as a pretest. PBL methodology was then applied throughout 16 learning sessions to the experimental group, while the control group received traditional learning methodologies. The same Bar-on test was then used as posttest to conduct measures for both groups. The results showed that there was significant influence of the PBL in the development of the emotional intelligence of the students of study.